2009
DOI: 10.1002/syn.20611
|View full text |Cite
|
Sign up to set email alerts
|

Single photon emission computed tomography experience with (S)‐5‐[123I]iodo‐3‐(2‐azetidinylmethoxy)pyridine in the living human brain of smokers and nonsmokers

Abstract: (1) the caudate head, the cerebellum, the cortex, and the putamen, utilizing both the Sign and Mann-Whitney U-tests; (2) the fusiform gyrus, the hippocampus, the parahippocampus, and the pons utilizing the Mann-Whitney U-test; and (3) the thalamus utilizing the Sign test. We conclude that 5-[ 123 I]IA is a safe, well-tolerated, and effective pharmacologic agent for human subjects to estimate high-affinity a4/b2 nAChRs in the living human brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 91 publications
2
16
0
Order By: Relevance
“…A T1-weighted SPGR (spoiled grass sequence; TR = 2110 ms, TE = 2.7 ms, 0.8 mm cubic voxels) covering the whole brain was used to define volumes of interest (VOIs) for the PET scan analysis; other T1- and T2-weighted images were also acquired as a part of a standardized battery (Brant-Zawadzki et al, 1992; Brašić et al, 2009) and were used to verify that participants met inclusion and exclusion criteria in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…A T1-weighted SPGR (spoiled grass sequence; TR = 2110 ms, TE = 2.7 ms, 0.8 mm cubic voxels) covering the whole brain was used to define volumes of interest (VOIs) for the PET scan analysis; other T1- and T2-weighted images were also acquired as a part of a standardized battery (Brant-Zawadzki et al, 1992; Brašić et al, 2009) and were used to verify that participants met inclusion and exclusion criteria in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Up-regulation can be achieved in animals by means of administration routes that are different from those of smokers and/or as nicotine doses that are much higher. Yet, it has been shown that smokers have higher cortical levels of nicotinic agonist binding and α4 subunit than non-smokers [121,122]. As the level of up-regulated subtypes persists for days after nicotine administration is stopped, it is possible that nAChR up-regulation plays a role during nicotine withdrawal.…”
Section: Regulation Of Native Subtypes By Chronic Nicotine Exposurementioning
confidence: 99%
“…Dynamic PET scans were performed over 90 minutes in a 3D mode with a GE Advance PET scanner following an IV bolus injection of 740 megabecquerels (MBq) [20 millicuries (20 mCi)] [ 11 C]MP. Three series of structural MRIs of the brain without contrast were performed 27 on a GE 1.5 T Signa MRI scanner. PET images were reconstructed using the back projection algorithm with a ramp filter using the software provided by the manufacturer correcting for attenuation, scatter, and dead-time.…”
Section: Methodsmentioning
confidence: 99%